GDF-15 and uEGF independently associate with CKD progression in children - Bartels, Julia; Tabatabaeifar, Mansoureh; Kirchner, Marietta; Azukaitis, Karolis; Doyon, Anke; Bayazit, Aysun; Düzova, Ali; Canpolat, Nur; Bulut, Ipek Kaplan; Obrycki, Lukasz; Ranchin, Bruno; Shroff, Rukshana; et al. (Kidney international. Reports, 2025)
Introduction - Currently, there is limited ability to predict the progression of chronic kidney disease (CKD) in children. Previously we reported that low levels of urinary epidermal growth factor (uEGF) predict CKD progression in children. In the present study, we investigated a novel serum biomarker, growth differentiation factor 15 (GDF-15), in 2 European pediatric CKD cohorts. We additionally explored the combined effect of GDF-15 and/or uEGF on CKD progression in children. - Methods - The association between serum GDF-15 levels and CKD progression was analyzed in 671 patients of the Cardiovascular Comorbidity in Children with CKD (4C) study, aged 6 to 17 years with an estimated glomerular filtration rate (eGFR) of 10 to 60 ml/min per 1.73 m2 at baseline, and median follow-up of 8 years. The composite end point was start of kidney replacement therapy, 50% eGFR loss, or eGFR < 10 ml/min per 1.73 m2. Results were validated in 329 participants from the ESCAPE trial. - Results - Higher GDF-15 levels were associated with an increased risk of CKD progression (hazard ratio: 1.40; 95% confidence interval [CI]: 1.10-1.77), independent of age, sex, baseline eGFR, proteinuria, and systolic blood pressure. Whereas adding either GDF-15 or uEGF individually to a model containing these variables improved model fit, combining both markers improved the model further. External validation in the ESCAPE cohort confirmed these results. - Conclusion - Serum GDF-15 and urine EGF levels may provide complementary information on the risk of CKD progression in children and might be included in future prognostic biomarker panels aimed at personalized, risk-stratified management of pediatric CKD.
Online verfügbar: 16. Juli 2025, Artikelversion: 8. Oktober 2025
Gesehen am 02.01.2026